2021
DOI: 10.1029/2020ja028405
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotail‐Inner Magnetosphere Transport Associated With Fast Flows Based on Combined Global‐Hybrid and CIMI Simulation

Abstract: Using the combined Auburn global hybrid simulation code in 3-D (ANGIE3D) and the Comprehensive Inner Magnetosphere-Ionosphere (CIMI) model, we investigate the self-consistent connection of fast flow injections from the tail plasma sheet and the inner magnetosphere under a southward IMF. In the dynamic run, the hybrid results provide the CIMI model with 3-D magnetic field and the electric potential at the high latitude ionosphere boundary as well as the full ion phase space distribution function at the CIMI out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Ukhorskiy et al (2018) used global MHD and test particle modeling to investigate particle interactions with a single bubble to demonstrate the importance of the mesoscale structure of the bubbles to trap the particles, whereas Cramer et al (2017) performed a more expansive study over a range of stormtime events to demonstrate the importance of bubbles in transport. In a series of papers representing the most self-consistent work to date (Lin et al, 2017(Lin et al, , 2021Cheng et al, 2020), global hybrid simulations were used to demonstrate that reconnection creates depleted bubbles that are anisotropic, non-Maxwellian, and not in equilibrium. However, spatial rescaling is necessary for global hybrid simulations to be computationally tractable and even then the duration of these simulations remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Ukhorskiy et al (2018) used global MHD and test particle modeling to investigate particle interactions with a single bubble to demonstrate the importance of the mesoscale structure of the bubbles to trap the particles, whereas Cramer et al (2017) performed a more expansive study over a range of stormtime events to demonstrate the importance of bubbles in transport. In a series of papers representing the most self-consistent work to date (Lin et al, 2017(Lin et al, , 2021Cheng et al, 2020), global hybrid simulations were used to demonstrate that reconnection creates depleted bubbles that are anisotropic, non-Maxwellian, and not in equilibrium. However, spatial rescaling is necessary for global hybrid simulations to be computationally tractable and even then the duration of these simulations remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…The DF is found to result in a reflected ion beam in the velocity distribution in the near‐tail region, as shown by Lin et al. (2021). Artemyev et al.…”
Section: Conclusion and Discussionmentioning
confidence: 53%
“…Contribution of DF to ion acceleration has also been found in our simulation, although the DF does not appear to provide a major energy enhancement. The DF is found to result in a reflected ion beam in the velocity distribution in the near-tail region, as shown by Lin et al (2021). Artemyev et al (2012) suggested that when ion gyroradii become comparable with the scales of the magnetic field, ions can gain energy through the resonance acceleration.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, here we present the results from a global 3D hybrid simulation using the AuburN Global hybrid CodE in 3D (ANGIE3D) hybrid code (Lin et al., 2014). The ANGIE3D code has been used in simulations of the solar wind‐magnetosphere coupling and global dynamics in the magnetosphere, including the magnetotail, magnetopause, and plasma sheet (Lin et al., 2014, 2017, 2021, 2022; Lu et al., 2016; Lu, Lin, et al., 2015; Lu, Lu, et al., 2015; Wang et al., 2020, 2021).…”
Section: Global Hybrid Simulationmentioning
confidence: 99%